Recognizing wrongs - Goldberg, John C. P., 1961-; Zipursky, Benjamin C., 1960- (The Belknap Press of Harvard University Press, 2020)
Much bemoaned and widely misunderstood, tort law provides an essential vehicle for injured parties to seek redress from wrongdoers and hold them accountable. John Goldberg and Benjamin Zipursky defend tort law against its critics and lay out comprehensively their increasingly influential "civil recourse" conception of tort.